1991
DOI: 10.1007/bf02026676
|View full text |Cite
|
Sign up to set email alerts
|

RARE-MR-urography in the diagnosis of upper urinary tract abnormalities in children

Abstract: RARE-MR-urography (Rapid Acquisition with Relaxation Enhancement) is a fast MR imaging technique (6.4 s/acquisition) that selectively depicts fluid by heavy T2-weighting. From 9/1989 to 11/1990, RARE-MR urograms were prospectively evaluated in the diagnosis of upper urinary tract abnormalities in 55 children. The method is performed in several planes and combined with a coronal, T1-weighted spin-echo sequence. Forty out of 42 kidneys with dilated renal pelvis, and 21 out of 24 dilated ureters were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 8 publications
0
37
0
2
Order By: Relevance
“…6b). This was expected to happen because, as we said before, MRU produces fluid-specific images [6, 8]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6b). This was expected to happen because, as we said before, MRU produces fluid-specific images [6, 8]. …”
Section: Resultsmentioning
confidence: 99%
“…Urinary tract obstruction results in static distended systems and is easily depicted [1]. Therefore we did not try to produce diuresis with furosemide, as distended systems produce clear fluid-specific images (water pictures) [6]. …”
Section: Resultsmentioning
confidence: 99%
“…Our minimum number of different projections was four. When adjusted angulations and various slice thicknesses were applied, the maximum number was by [10][11][12][13][14][15]. The total amount of time for all these acquisitions was then about 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984 it was demonstrated that single-shot modification RARE can be used to depict only water-containing structures such as the spinal canal, kidney, cysts, etc. This technique was termed RAREhydrography, or, depending on its applications, RAREmyelography (10) or RARE-urography (11) mainly applied in neuroradiology and pediatric urology. Singleshot RARE has been implemented on a 1.0 T whole body-imager (Magnetom Impact, Siemens, Erlangen Germany) allowing multiplanar single-shot acquisitions with a variable slice thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[5,2,3,6,7,8,4] The most common MR urographic techniques for displaying the urinary tract can be divided into two categories: Static-fluid MR urography and Excretory MR urography. Static-fluid MR urography makes use of heavily T2-weighted sequences to image the urinary tract as a static collection of fluid, can be repeated sequentially (cine MR urography) to better demonstrate the ureters in their entirety and to confirm the presence of fixed stenosis, and is most successful in patients with dilated or obstructed collecting systems.…”
mentioning
confidence: 99%